2016
DOI: 10.1007/s10157-016-1338-9
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of perivascular lymphatic vessels in preservation of kidney allograft function

Abstract: High perivascular lymphatic density is associated with favourable kidney allograft function. The perivascular lymphatic network may be involved in inhibition of allograft fibrosis and stabilization of graft function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…18 Another study demonstrated kidney transplants with higher perivascular lymphatic density had a reduced proportion with progression of interstitial fibrosis/tubular atrophy grade from 3-12 months posttransplant and was associated with a reduced rate of estimated glomerular filtration rate decline after 12 months. 19 In line with this, VEGF-C overexpression in mouse kidney allografts significantly attenuated acute rejection 20 ( Figure 2B). Overall, perivascular lymphatic density or lymphatic density in proximity to TLOs may be the best indicators of early outcomes in kidney transplants, in part, related to their ability to provide a route for immune cell emigration.…”
Section: Kidney Transplantationsupporting
confidence: 69%
See 1 more Smart Citation
“…18 Another study demonstrated kidney transplants with higher perivascular lymphatic density had a reduced proportion with progression of interstitial fibrosis/tubular atrophy grade from 3-12 months posttransplant and was associated with a reduced rate of estimated glomerular filtration rate decline after 12 months. 19 In line with this, VEGF-C overexpression in mouse kidney allografts significantly attenuated acute rejection 20 ( Figure 2B). Overall, perivascular lymphatic density or lymphatic density in proximity to TLOs may be the best indicators of early outcomes in kidney transplants, in part, related to their ability to provide a route for immune cell emigration.…”
Section: Kidney Transplantationsupporting
confidence: 69%
“…Sequential biopsies in human kidney transplants revealed that grafts with higher lymphatic densities within nodular areas of cellular infiltrates (resembling TLOs) had improved kidney functional outcomes compared to those with lower LV density 1 year posttransplant . Another study demonstrated kidney transplants with higher perivascular lymphatic density had a reduced proportion with progression of interstitial fibrosis/tubular atrophy grade from 3‐12 months posttransplant and was associated with a reduced rate of estimated glomerular filtration rate decline after 12 months . In line with this, VEGF‐C overexpression in mouse kidney allografts significantly attenuated acute rejection (Figure B).…”
Section: Role Of Lymphangiogenesis In Solid Organ Transplantationmentioning
confidence: 64%
“…We have previously reported that a high perivascular lymphatic density in kidney transplant patients is associated with the kidney allograft prognosis. 8 The best known factors to promote lymphangiogenesis are vascular endothelial growth factor (VEGF)-C and VEGF-D. VEGF-C binds to VEGF receptor-2 (VEGFR-2) and VEGFR-3, which plays a crucial role in proliferation, migration, and survival of lymphatic endothelial cells (LECs) via VEGFR-3, 9 and has lesser effects on blood vessels via VEGFR-2. [10][11][12] VEGF-C deficiency results in embryonic death of mice.…”
mentioning
confidence: 99%
“…Although our study demonstrated the lymphangiogenesis could deteriorate the function of renal allografts, some previous studies reported that lymphangiogenesis could prolong the life span of recipients with better renal functions both in mouse and human kidney transplant, which is totally contrary to our findings ( 35 , 55 ). In parallel, a clinical study revealed human biopsy studies demonstrated kidney transplants with higher perivascular lymphatic density had a reduced proportion with progression of interstitial fibrosis/tubular atrophy grade ( 56 ). These studies held the perspective that LVs give play to provide excurrent pathways for cellular infiltration, and thus prevent continuous alloimmune responses in renal allografts.…”
Section: Discussionmentioning
confidence: 99%